STUDI TENTANG KAITAN DI KOTA PARIAMAN - Afria, Reni; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The aim of this research is to describe the tools and materials, the making techniques and the types of products which is produced by the crochet industry in the Pariaman city. The method used is a qualitative method. The type of data in the form of primary data and secondary data. Informants are the leaders and craftsmen each industry. The technique of collecting data through observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. Extension of the validity of the data with observations, increased observation and triangulation. Result: Equipment and Materials used consist of a crochet hook with numbers 8, 9, 1/0 and 2/0, sewing machines, stitch machine and cotton yarn, white and cream, with a yarn numbering numbers 6 and 9. Process roll thread there are two ways, namely utilizing limbs and used yarn mill player. The usage of crochet hook number 1/0 and 2/0 is for the yarn number 9. Crochet hook number 8 and number 9 for number 6. Yarn making technique used the initial stitch, chain stitch, tightly stitch, closely half stitch, single crochet, double crochet, and picot stitch. Type of connection used a regular crochet, irish crochet, american crochet, the crochet stitch. It produced tablecloths, cover gallon, souvenirs and products related to fashion. Kata kunci: Studi, Industri, Kaitan